Multi-omics reveals total flavones from Abelmoschus manihot (L.) Medik. [Malvaceae] ameliorate MAFLD via PI3K/AKT/mTOR-mediated autophagy - Lv, Chao; Zhao, Lei; Hou, Jiani; Sun, Hongyin; Li, Zhongsha; Wu, Yuesong; Shi, Peizheng; Xiao, Yaping; Xie, Yunjin; Su, Wei; Yin, Mingzhu (Frontiers in Pharmacology, 2025)
IntroductionMetabolic-associated fatty liver disease (MAFLD) has emerged as a global health crisis, which is characterized by hepatic lipid accumulation, inflammation, and fibrosis. Currently, effective therapeutic strategies for MAFLD are still scarce.MethodsThis study aimed to explore the hepatoprotective effects and underlying mechanisms of total flavones from Abelmoschus manihot (L.) Medik. (Malvaceae), abbreviated as TFA, in the context of MAFLD. Ultra-high-performance liquid chromatography-quadrupole orbitrap mass spectrometry (UHPLC-QTOF-MS) was used to identify the metabolites in TFA. MAFLD mice induced by a high-fat diet were treated with TFA at doses of 50 and 100 mg/kg. Body weight gain, hepatic lipid accumulation, and serum levels of alanine transaminase (ALT), aspartate transaminase (AST), total cholesterol (TC), and triglycerides (TG) were determined. Histological analysis was performed to evaluate hepatic steatosis, fibrosis, as well as the levels of inflammatory cytokines (IL-6, TNF-α) and antioxidant markers (SOD, GSH). Transcriptomic and metabolomic analyses were carried out to explore the molecular mechanisms. In vitro studies were conducted in HepG2 cells, and the role of autophagy was investigated using the autophagy inhibitor 3-MA.ResultsUsing UHPLC-QTOF-MS, 56 metabolites were identified in TFA, including hyperoside, rutin, and quercetin derivatives, which possess anti-lipidemic and anti-inflammatory properties. In MAFLD mice, TFA treatment significantly decreased body weight gain, hepatic lipid accumulation, and the serum levels of ALT, AST, TC, and TG. Histological analysis demonstrated that TFA alleviated hepatic steatosis and fibrosis, with decreased levels of inflammatory cytokines and increased antioxidant markers. Transcriptomic and metabolomic analyses indicated that TFA regulated nucleotide metabolism, pyrimidine metabolism, and the PI3K/AKT/mTOR signaling pathway. In HepG2 cells, TFA inhibited palmitic acid/oleic acid-induced lipid deposition and the production of reactive oxygen species (ROS). Mechanistically, TFA activated autophagy through the inhibition of PI3K/AKT/mTOR phosphorylation, as demonstrated by the increased LC3II/I conversion and decreased p62 expression. The autophagy inhibitor 3-MA abolished the protective effects of TFA.DiscussionOur findings suggest that TFA ameliorates MAFLD via promoting PI3K/AKT/mTOR-mediated autophagy. The metabolites identified in TFA might contribute to its multi-target therapeutic effects. Considering the limited treatment options for MAFLD, TFA exhibits great potential as a novel therapeutic agent for MAFLD intervention, thus justifying further preclinical and clinical investigations.